Pharm-D community pharmacy visit - Maryam, Saleh; Amna, Bugrain; Hana, Habib (Libyan International Medical University Faculty of Pharmacy, 2018)
Pharm-D community pharmacy visit
Pharm-D students receive training session in one of the typical community pharmacies ( called Alyansoun), as a part of their educational program for pharmacy practice which is one of the important components of the sixth block in the second year.
Keywords: community activity; Pharm-D; pharmacy visit